(untitled) (mathematica didactica, 2026)
This paper evaluates a component of a learning environment developed using DSR for the informed use of search engines and AI chatbots in mathematics lessons at primary level, which deals with algorithmic bias and machine learning. For this purpose, a multiple case study is conducted using qualitative survey and evaluation methods. TDS is used as a framework to support the didactic design and combined with AiC to analyse learning processes on a micro-analytical level. The results indicate that the functionality and the quality of the output of an AI system should be analysed more intensively with the learners.